The use of trimeric isoleucine-zipper fusion proteins to study surface-receptor-ligand interactions in natural killer cells - Stark, Sebastian; Flaig, Rüdiger Marcus; Sandusky, Mina; Watzl, Carsten (Journal of immunological methods, 2005)
The ligands for several activating natural killer (NK) cell receptors have not been identified to date. Soluble receptor fusion proteins can be used to stain target cells for the presence of these unidentified ligands. Here, we describe the generation and use of soluble type I NK cell receptor isoleucine-zipper (ILZ) fusion proteins of the immunoglobulin (Ig) superfamily. ILZ-fusion proteins are easy to produce and purify. They form trimeric complexes in solution and display a higher binding avidity than classical immunoglobulin-fusion proteins. ILZ-fusion proteins do not interact with Fc-receptors and can therefore be used to block receptor-ligand interactions in cellular assays. This makes ILZ-fusion proteins a valuable tool to study receptor-ligand interactions in NK cells and other cellular systems.